N,N-Dimethyl-3β-hydroxycholenamide Reduces Retinal Cholesterol via Partial Inhibition of Retinal Cholesterol Biosynthesis Rather Than its Liver X Receptor Transcriptional Activity - El-Darzi, Nicole; Astafev, Artem; Mast, Natalia; Saadane, Aicha; Lam, Morrie; Pikuleva, Irina A. (Frontiers in Pharmacology, 2018)
N,N-dimethyl-3-hydroxycholenamide (DMHCA) is an experimental pharmaceutical and a steroidal liver X receptor (LXR) agonist, which does not induce undesired hepatic lipogenesis. Herein, DMHCA was evaluated for its retinal effects on normal C57BL/6J and Cyp27a1-/-Cyp46a1-/- mice; the latter having higher retinal total and esterified cholesterol in addition to retinal vascular abnormalities. Different doses and two formulations were used for DMHCA delivery either via drinking water (C57BL/6J mice) or by oral gavage (Cyp27a1-/-Cyp46a1-/- mice). The duration of treatment was one week for C57BL/6J mice and two or four weeks for Cyp27a1-/-Cyp46a1-/- mice. In both genotypes, the higher DMHCA doses (37-80 mg/kg of body weight/day) neither increased serum triglycerides nor serum cholesterol but altered the levels of retinal sterols. Total retinal cholesterol was decreased in the DMHCA-treated mice, mainly due to a decrease in retinal unesterified cholesterol. In addition, retinal levels of cholesterol precursors desmosterol and lathosterol were increased and decreased, respectively, in Cyp27a1-/-Cyp46a1-/- mice. In both genotypes, DMHCA effect on retinal expression of the LXR target genes was only moderate and gender-specific. Collectively, the data obtained provide evidence for a decrease in retinal cholesterol as a result of DMHCA acting in the retina as an enzyme inhibitor rather than a LXR transcriptional activator. DMHCA appears to partially inhibit the cholesterol biosynthetic enzyme ∆24-dehydrocholesterol reductase rather than activate LXRs and upregulate the expression of the target genes involved in reverse cholesterol transport. Our results also point to a possible inhibition of a retinal enzyme hydrolyzing cholesterol esters. The identified DMHCA dosages, formulations, and routes of delivery as well as the specific effects on the retina should be considered in future studies using DMHCA as a potential therapeutic for age-related macular degeneration and diabetic retinopathy.